2016
DOI: 10.4028/www.scientific.net/kem.682.182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Addition of Glassy Carbon on the Structure and Properties of ZrO<sub>2</sub>-Y<sub>2</sub>O<sub>2</sub> Coatings

Abstract: The effect of the addition of glassy carbon on the structure and properties of ZrO2-Y2O2 coatings deposited at the graphite substrate has been investigated. The coatings were deposited by plasma spraying method in an industrial company Plasma System SA Silesian Siemianowice using MIM40 equipment. The microstructure of coatings was investigated by light microscopy (MO), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Abrasion was carried out with the use of tribological tester Duc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Unfortunately, coatings obtained by plasma spraying are characterized by high levels of porosity. To confer adequate smoothness to the surface layer, an additional layer of glassy carbon is applied; this eliminates the problem of roughness and/or porosity, eliminating also the risk that the surface might be wetted by metals such as Al, Cu, Zn, Ag, or Sn [11,12]. Tungsten is a chemical element characterized by high hardness and a very high melting point (3600°C).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, coatings obtained by plasma spraying are characterized by high levels of porosity. To confer adequate smoothness to the surface layer, an additional layer of glassy carbon is applied; this eliminates the problem of roughness and/or porosity, eliminating also the risk that the surface might be wetted by metals such as Al, Cu, Zn, Ag, or Sn [11,12]. Tungsten is a chemical element characterized by high hardness and a very high melting point (3600°C).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of all of these benefits, the low thermal conductivity [6,7] can result in coating detachment from molds during casting. A solution to this problem is introducing a large amount of graphite to the coating composition or applying an outer layer of glassy carbon, which also shows a low degree of wettability by liquid copper [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…The studies carried out by the authors have indicated the possibility of using coatings based on zirconium oxide and aluminium oxide [4,5]. The ceramic coatings of Al 2 O 3 and Zr 2 O 3 -Y 2 O 3 applied by plasma spraying are characterized by low wettability in contact with liquid copper, micrometer thickness, and good abrasion resistance.…”
Section: Introductionmentioning
confidence: 99%